Immune Deficiency in Fetal Alcohol Syndrome - Johnson, Sharron; Knight, Richard; Marmer, Daniel J; Steele, Russell W (Pediatric research, 1981)
In a review of 13 documented cases of fetal alcohol syndrome (FAS), an increased incidence of life-threatening bacterial infections as well as a propensity to minor infections was observed. Five of 13 patients had had at least one episode of pneumonia, two had meningitis, and one had sepsis. A comprehensive immunologic evaluation of FAS was completed, and results were compared to an age-matched control group of children with intrauterine growth retardation without FAS. Children with FAS were shown to have decreased E rosette-forming lymphocytes (35 +/- 5% versus 55 +/- 5% or 1328 +/- 274 versus 2333 +/- 112 per mm3), low EAC rosette-forming lymphocytes (15 +/- 2% versus 18 +/- 1% or 524 +/- 109 versus 740 +/- 75 per mm3), and diminished mitogen-induced stimulation responses to mitogens: 31616 +/- 5337 versus 58076 +/- 4455 cpm for phytohemagglutinin, 17582 +/- 5436 versus 35018 +/- 5346 for pokeweed mitogen, and 32460 +/- 7044 versus 54996 +/- 5531 for concanavalin A, P less than 0.05. Nine patients had dysgammaglobulinemia, FAS subjects also had a marked eosinophilia (624 +/- 154 versus 72 +/- 27 mm3). Other parameters of immune function including absolute lymphocyte and neutrophil counts, total hemolytic complement, delayed cutaneous hypersensitivity, and nitroblue tetrazolium dye reduction assays, were not different from control children. Impairment of immunity may explain an increased susceptibility to infection in FAS.